Awake and (Only Just) Aware? A Typology, Taxonomy, and Holistic Framework for Withdrawing Clinically Assisted Nutrition and Hydration in the Minimally Conscious State. (13th December 2017) - Samanta, Jo; Samanta, Ash
Abstract: Decisions to withdraw clinically assisted nutrition and hydration (CANH) from people in the minimally conscious state are predicated on the question as to whether it is in the individual's best interests to continue with CANH and determined traditionally using a 'balance sheet' approach. The emerging case law in this area suggests that decisions may appear inconsistent and lack sufficient certainty and clarity of process. Using an analysis of statute, common law and academic commentary we articulate a typology for the elements that tend to engage in these decisions. Next, we construct a taxonomy of overarching legal and ethical issues and then proceed to develop a novel framework for holistic decision-making. We validate this on the principle upon which it is grounded: coherent weighting of elements and theoretical proof of concept. The framework has potentially far-reaching benefits that include consistency and transparency of decision-making, thereby enabling a more uniform judicial approach. We suggest this as a foundational paradigm for decision-making in this context.